Computational Thinking : Vocational Students Abstraction in Solve the Geometric Pattern Problem - Swasti Maharani; Annisa Nurhidayati Mu'arif; Tri Andari (STAI Hubbulwathan Duri, 2023)
The aim of this research is to explore the students' abstraction in solving geometric pattern problems based on gender. The subjects are 31 students in Grade X Multimedia, consisting of 12 male students and 19 female students. This research is qualitative descriptive research. Geometric pattern problems and interview guides are the instruments in this research. The results show that female students can master the concept of geometric patterns to solve the problem easily. Beside, they use the knowledge to represent the object and write the general term well. For male students are still not able to master the concept. In the several stages, they still using the manual way to solve the problem and still not able to represent the object well. In the problem-solving stage, they still do mistakes. A recommendation for future study is to explore further about students' abstraction in other mathematics problems.